Recent Advances in Carbon Dots for In Vitro/Vivo Fluorescent Bioimaging: A Mini-Review - He, Chen; Lin, Xiaofeng; Mei, Yanqiu; Luo, Yan; Yang, Min; Kuang, Ying; Yi, Xiaoqing; Zeng, Weijia; Huang, Qitong; Zhong, Bin (Frontiers in Chemistry, 2022)
As a new type of “zero-dimensional” fluorescent carbon nanomaterials, carbon dots (CDs) have some unique optical and chemical properties, they are being explored for a variety of applications in bio-related fields, such as bioimaging, biosensors, and therapy. This review mainly summarizes the recent progress of CDs in bioimaging. The overview of this review can be roughly divided into two categories: (1) In vitro bioimaging based on CDs in different cells and important organelles. (2) The distribution, imaging and application of CDs in mice and zebrafish. In addition, this review also points out the potential advantages and future development directions of CDs for bioimaging, which may promote the development of CDs in the field of bioimaging.